Regional left ventricular wall motion from first-pass radionuclide angiocardiography using an Anger camera. Experimental and clinical study. Issue 5 (November 1980) - Walton, S; Donaldson, E A; Rowlands, D J; Shields, R A; Testa, H J; Wrigley, C
Abstract : Experimental studies with a balloon phantom, and clinical studies were performed to evaluate first-pass radionuclide angiocardiography using a gamma camera in the assessment of regional wall motion. The phantom studies showed that choice of isocount contour was not critical in edge detection. Adequate count densities could be achieved, but only at the expense of temporal resolution. The clinical studies disclosed a good correlation with radiography in normal subjects and those with diffuse ventricular disease but a poor correlation in subjects with localised abnormalities of wall motion.